2015
DOI: 10.1093/hmg/ddv053
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the latent TGF-beta binding protein 3 (LTBP3) gene cause brachyolmia with amelogenesis imperfecta

Abstract: Inherited dental malformations constitute a clinically and genetically heterogeneous group of disorders. Here, we report on four families, three of them consanguineous, with an identical phenotype, characterized by significant short stature with brachyolmia and hypoplastic amelogenesis imperfecta (AI) with almost absent enamel. This phenotype was first described in 1996 by Verloes et al. as an autosomal recessive form of brachyolmia associated with AI. Whole-exome sequencing resulted in the identification of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 39 publications
1
53
0
2
Order By: Relevance
“…Our previous study reported that four unrelated families had mutations in LTBP3, which probably produced AI and brachyolmia phenotypes. This highlights the role of LTBP-3 and TGF-b signaling in amelogenesis (24). Here, our findings of morphological changes within all tooth components, including enamel and ameloblasts, of Ltbp3-knockout mice supports multiple roles of LTBP-3 in odontogenesis.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Our previous study reported that four unrelated families had mutations in LTBP3, which probably produced AI and brachyolmia phenotypes. This highlights the role of LTBP-3 and TGF-b signaling in amelogenesis (24). Here, our findings of morphological changes within all tooth components, including enamel and ameloblasts, of Ltbp3-knockout mice supports multiple roles of LTBP-3 in odontogenesis.…”
Section: Discussionsupporting
confidence: 71%
“…In another family, two sisters with homozygous-recessive truncating mutations in LTBP3 also had oligodontia, short stature, and mitral valve prolapse (23). Our published report identified recessive hypomorphic LTBP3 mutations (including deletion, nonsense, and aberrant splice mutations) in patients with dental anomalies and short stature (MIM; 601216) (24) or Verloes Bourguignon syndrome (25). Using the adult Ltbp3-/-mouse model to characterize all dental hard-tissue components, we previously described very thin or absent enamel in both incisors and molars (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both heterozygotes and homozygotes in this family had short stature though not significantly below the Pakistani average. Subsequently, homozygous or compound heterozygous mutations in LTBP3 (five distinct mutations: nonsense, splice site and deletions resulting in frameshifts) were identified in four families with hypoplastic amelogenesis imperfecta, short stature and brachyolmia 29. All heterozygous parents were reported as healthy with normal dentition.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of different genetic mutations can be responsible for these heritable diseases . Pitting‐ and plane‐form enamel hypoplasia are common, but abnormal enamel density, thickness and discoloration are also associated with different forms . To differentiate between different types of AI, clinical, histological and radiographic methods have been used …”
Section: Introductionmentioning
confidence: 99%